KEBIJAKAN PEMERINTAH DESA DALAM MENCEGAH PERNIKAHAN DINI DI DESA GONDANG KECAMATAN GANGGA KABUPATEN LOMBOK UTARA: Village Government Policy In Preventing Early Marriage In Gondang Village, Gangga District, North Lombok Regency - Agus Suhaidi Ibrahim (Yayasan Al-Amin Qalbu, 2025)
Early marriage is a social issue that remains a major challenge in developing the quality of human resources, particularly in Gondang Village. Therefore, policies and regulations are needed to address this issue. The purpose of this study is to examine village government policies in preventing early marriage in Gondang Village, Ggangga District, North Lombok Regency. This research is a public policy analysis of village government policies to prevent early marriage. The analysis found that the role of village government has proven to be very strategic in designing and implementing policies that are more responsive to the community. Although the central government has set a minimum age for marriage as stipulated in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974, preventive efforts at the village level remain the spearhead in preventing child marriage. Giddens' structuration theory and Zimmerman's empowerment theory reinforce the view that social behavior can change when communities have the knowledge, capacity, and space to engage in development processes. Preventing early marriage requires a multi-sectoral, community-based, and sustainable approach. Village policies are a crucial instrument, but the success of prevention efforts depends heavily on collaboration between village governments, communities, educational institutions, community health centers (Puskesmas), the Religious Affairs Office (KUA), and other stakeholders